ANALISIS CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS MELALUI MEKANISME VARIABEL MODERASI DENGAN MANAJEMEN LABA - Ade Onny Siagian; Adler H. Manurung; Nera Marinda Machdar (International Forum of Researchers and Lecturers, 2023)
The purpose of this study was to examine the effect of corporate governance mechanisms on financial distress with earnings management as a moderating variable. The population used consists of companies in the infrastructure, utility, and transportation sectors listed on the Indonesia Stock Exchange in 2020 – 2022. This study uses a causality study with purposive sampling and analyzed by logistic regression. The results of this study indicate that institutional ownership has a significant negative effect on financial distress, while the audit committee has no effect on financial distress. Earnings management as a moderating variable weakens the relationship between institutional ownership and financial distress but is not significant. Meanwhile, earnings management strengthens the relationship of the audit committee to financial distress but is not significant. The implication of this research is that companies need to increase the role and function of supervision and audit committees to minimize the risk of financial distress. Although earnings management is not able to moderate institutional ownership and audit committees, companies still need to improve supervision, especially on the financial reporting process to avoid the risk of financial distress.